Epidemiological profile and follow-up of patients with pulmonary disease by non-tuberculous mycobacteria in Baixada Santista area, São Paulo - Andréa Gobetti Vieira Coelho; Ana Carolina Chiou; Heloisa da Silveira Paro Pedro; Susilene Maria Tonelli Nardi; Erica Chimara (Einstein (São Paulo), 2022)
ABSTRACT Objective To present the frequency and species diversity of non-tuberculous mycobacteria, estimate the prevalence of non-tuberculous mycobacterial pulmonary disease, describe the epidemiological profile, and determine the follow-up of patients with non-tuberculous mycobacterial pulmonary disease living in a region with a high burden of tuberculosis. Methods This a retrospective cohort observational study using data records obtained from the Instituto Adolfo Lutz - Santos and from the São Paulo Sistema de Vigilância de Tuberculose do Estado de São Paulo in the period between 2000 and 2009. The studied variables were: socio-demographic characteristics, current and past history of tuberculosis, aspects related to diagnosis, and treatment and associated diseases. Results We included 319 non-tuberculous mycobacteria isolates in the study, corresponding to 257 patients. The species Mycobacterium kansasii (28.5%) and Mycobacterium fortuitum (16.6%) presented the higher occurrence. In 10.9% (24) of the patients, there was a criterion for confirming a case of pulmonary disease due to non-tuberculous mycobacteria. In relation to gender and age, male and individuals over 50 years old were the most frequent. Considering the confirmed cases, 47.8% had a past history of tuberculosis. Conclusion The lack of information about the cases is evident, since pulmonary disease due to non-tuberculous mycobacteria is not mandatory. The therapeutic regimen according to the identified species is fundamental for success in combating the infections caused by non-tuberculous mycobacteria. Besides that, information about the regional epidemiology of pulmonary disease caused by non-tuberculous mycobacteria and the search for associations with other comorbidities are important to establish the correct treatment. In order to improve surveillance of pulmonary diseases by non-tuberculous mycobacteria, we suggest the implantation of a sentinel surveillance and of population-based studies.